(untitled) (Annals of Medical Research, 2021)
Aim: Prolonged mechanical ventilation (PMV) after cardiovascular surgeries is associated with morbidity and mortality. The aim of the study was to determine the risk factors for postoperative PMV (PPMV) after left ventricular assist device (LVAD) surgery.Material and Methods: We retrospectively analyzed the data of patients who underwent LVAD surgery between 2011 and 2016. Prolonged mechanical ventilation was defined as postoperative tracheal extubation 24 hours after the patient is admitted to the ICU. Patients were divided into two groups whether they were extubated within 24 hours of surgery or extubated after 24 hours following surgery.Results: During the study period, a total of fifty-seven patients were admitted to ICU. Fifty-seven patients’ data were screened. The mean age of the 57 patients enrolled was 44.6 ± 16.1 years. Of them, 82% were male, and 54 (95%) patients had dilated cardiomyopathy diagnosis. A total of 26 (46%) patients required PPMV. The two groups were similar in terms of demographics, duration of surgery, postoperative LVAD flow rates, presence of preoperative MV, infections, and circulatory support devices (p > 0.05). Patients who required PPMV underwent more revision surgeries [14 (54%) vs. 2 (7%), p 0.001] and had higher incidences of acute kidney injury (AKI) on the first day after the surgery [13 (50%) vs. 4 (13%), p = 0.003] compared with those who did not require PPMV. Furthermore, the patients who required PPMV also required more renal replacement therapies postoperatively [12 (46%) vs. 5 (16%), p = 0.02] and had longer intensive care unit stay (30.1±25.2 days vs. 14.0 ±11.4 days, p = 0.002) and had higher hospital mortality (58% vs. 35%, p = 0.043) and 30-day mortality (38% vs. 16%, p = 0.042) than those who did not require PPMV. Logistic regression analysis revealed postoperative AKI as an independent risk factor for PPMV (OR = 0.223, 95% CI 0.067–0.743, p = 0.015).Conclusion: Our results revealed that almost half of the patients who underwent LVAD surgery required PPMV. AKI on the first day following surgery is an independent risk factor for PPMVs.